Half-Day Visit to Solok-Sawahlunto Area, Ombilin Basin: A Short Observation on Non-marine Depositional Sequences - RM Iman Argakoesoemah; Didit Ariady Firmansyah (Berita Sedimentologi, 2011)
This is a brief note of our visit to Solok, Sawahlunto area, Ombilin Basin on November 8, 2008 for the purpose of broadening our knowledge on non-marine depositional sequence and its relationship to the development of hydrocarbon petroleum system in the region. Exposure of the outcrops is excellent in the form of accessibility and vertical extent of the stacked sequences.Unfortunately, as the time was limited, there was no opportunity to conduct sufficient detailed description of the outcrops. However, several notes of broad observation of the outcrops were made. Part of them is discussed in this paper.A total of eight (8) locations (=STA) were visited during this half-day reconnaissance trip. The traverse began from Solok using a car towards the northeast to locations 1 to 8 following the existing main road to Sawahlunto. The outcrops are easilyaccessed and visible from the main road. Some of the outcrops are located immediately on the edge of the road.